Food Safety Knowledge, Attitudes, and Practices Among Jordan Universities Students During the COVID-19 Pandemic - Osaili, Tareq M.; Al-Nabulsi, Anas A.; Taybeh, Asma' O. (Frontiers in Public Health, 2021)
Objective: This study aimed to evaluate food safety knowledge, attitudes and practices (KAP) amongst university students in Jordan and changes in food-related behaviors during the COVID-19 pandemic. Correlation between food safety KAP scores and general characteristics of university students was also evaluated. Methods: A cross-sectional study was conducted where an Internet-based questionnaire was distributed through social media platforms. The sample consisted of 1,739 respondents from 29 Jordanian universities. The participants completed a 58-item questionnaire covering demographical characteristics and different food safety aspects which were namely “COVID-19 food-related attributes,” “food cooking and storage,” “personal hygiene.” “cross-contamination prevention/disinfection procedures.” and “restaurant hygiene.” Descriptive statistics, Chi square tests and binary logistic analysis were used to assess the data. Results: The sample consisted of 67.2% females with a mean age of 21.3 ± 1.8 years. The average overall score of the tested aspects was 14.1/34.0 which corresponds to 41.3% of the questions being answered correctly. The percentage of correct answers of “COVID-19 food-related attributes,” “food cooking and storage,” “cross-contamination prevention/disinfection procedures,” “personal hygiene” and “restaurant hygiene” was 56.8, 36.6, 28.4, 44.6. and 36.9%, respectively. A significant (P <0.05) association between respondents' food safety KAP scores and gender, marital status, university degree, employment status, self-rating of food safety knowledge, and the source of food safety information. Conclusion: University students in Jordan had insufficient KAP scores which is a concerning trend during the pandemic. Teaching fundamentals of food safety in the form of short courses/ lectures is recommended.